Sustainability Practices and Performance in the Manufacturing Sector: The Role of Paradoxical Mindset - Droup, Ismail; Jusoh, Ahmad; Alghamdi , Sami Ahmed; Nor, Khalil Md (Journal of Ecohumanism, 2024)
Sustainability has recently become a key to long-term business success. Firms are applying sustainability practices to improve their sustainable performance. However, the application of these practices has led plant managers to face the competing demands of sustainability objectives. A paradoxical mindset may help these manager to respond to such competing demands. However, the existing literature lacks empirical research on the role of a paradoxical mindset in sustainability practices and related performance paths. To fill this research gap, our paper aims to test the direct relationship between sustainability practices and connected performance. Furthermore, the study also aims to explore how a paradoxical mindset affects this direct relationship. The data was collected from 224 manufacturing plants and analyzed using Structural Equation Modeling (SEM-Smart-Pls). The findings revealed that Sustainability practices positively influence economic, environmental performance, and social performance. Furthermore, this study discovered that a paradoxical mindset moderates the relationships between sustainability practices and environmental performance. however, the study did not find any empirical evidence to support the effect of the interaction of paradoxical mindsets and sustainability practices on social performance. This study attempts to fill certain gaps in operations management literature and provides researchers and manufacturing managers with a deeper understanding of the roles of sustainability practices and the paradoxical mindset of the plant' managers in the manufacturing sector.